Evaluating the impact of gut microbiota, circulating cytokines and plasma metabolites on febrile seizure risk in Mendelian randomization study - Chenyue Zhao; Huiqin Xue; Min Guo; Hao Yue; Xintong Chen; Jingbo Gao (Scientific Reports)
Abstract Febrile seizures (FS) is the most common type of convulsion in infants and preschool children. This study aimed to investigate the associations between gut microbiota abundance, plasma metabolites, circulating cytokines, and FS. Summary statistics of 211 gut microbiota traits, 1,400 plasma metabolite traits, 91 circulating cytokine traits, and FS were obtained from publicly available genome-wide association studies. Two-sample Mendelian randomization (MR) analysis and causality was inferred using Inverse variance-weighted (IVW), Weighted median, MR-Egger, simple mode-based estimate and weighted mode-based estimate 5 methods. Several sensitivity analyses were also used to ensure the robustness of the results. Furthermore, mediation analysis was used to determine the pathway from gut microbiota to FS mediated by plasma metabolites and circulating cytokines. MR revealed the associations of 1 gut microbiota (phylum Verrucomicrobia), 4 circulating cytokines and 50 plasma metabolites on FS. Based on the known pathogenic metabolites, we observed that the tryptophan, androgen, and sphingolipids pathways are associated with FS. Mediation analysis revealed 1 strongly documented plasma metabolite (Ascorbic acid 2-sulfate) as a mediator linking “gut microbiota to plasma metabolite to FS”. Sensitivity analysis was represented no heterogeneity or pleiotropy in this study.Our study provides some causal evidence concerning the effects of the gut microbiota, circulating cytokines, and plasma metabolites on FS, which needs to be verified in randomized controlled trials. These biomarkers provide new insights into the underlying mechanisms of FS and contribute to its prevention, diagnosis, and treatment.